Cardiovascular risk and mortality in men receiving testosterone replacement therapy for Klinefelter syndrome in Denmark: a retrospective cohort studyResearch in context - Simon Chang; Lars Pedersen; Anne Skakkebæk; Agnethe Berglund; Claus H. Gravholt (The Lancet Regional Health. Europe)
Summary: Background: Men with Klinefelter syndrome (KS) have hypogonadism, increased morbidity, and excess mortality. Testosterone replacement therapy (TRT) has the potential to alleviate this burden. We assessed the risk of major cardiovascular events (MACE) and mortality in KS according to TRT exposure. Methods: We performed a nationwide registry based matched cohort study. We compared incidences of MACE and mortality between TRT exposed (KS-TRT) or unexposed KS (KS-non-TRT), and a male background population comparison cohort. The study period was from 1 January 1994 to 31 December 2022. Findings: We identified 557 KS-TRT, and matched these with unexposed men with KS born the same year (total KS n = 950). We similarly identified a comparison cohort of 50,150 men from the background population matched on month and year of birth. Median age at entry for KS-TRT was 31.1 years (interquartile range; 19.9–40.0) and median follow-up time was 12.9 years (interquartile range; 7.5–20.7). KS-TRT was associated with lower all-cause mortality (adjusted hazard ratio (95% CI); 0.56 (0.37–0.85)), with mortality in KS-TRT comparable to the comparison cohort (hazard ratio (95% CI); 1.27 (0.91–1.79)). Incidence of MACE was comparable between KS-TRT and KS-non-TRT. Interpretation: TRT could alleviate excess mortality in KS and appears safe regarding cardiovascular risk. Today, most men with KS go undiagnosed, missing proper medical attention. There is a dire need for a policy change to ensure timely diagnosis and treatment in all men with KS. Funding: The A.P. Moller Foundation, Fonden af 17-12-1981, Danish Diabetes and Endocrine Academy, Novo Nordisk Foundation, the Independent Research Fund Denmark, Sygesikringen danmark.